Computer aided simulation and experimental investigation of the machinability of Al 6065 T6 during milling operation - Daniyan, Ilesanmi; Ale, Felix; Fameso, Festus; Mrausi, Siviwe; Ndambuki, Julius (International journal of advanced manufacturing technology, 2024)
Aluminium alloy is increasingly being used in the industries because of its high strength to weight and corrosion resistance ability. However, there is a need to investigate its machinability to ensure that it will meet the quality and functional requirements for its intended applications. Hence, this study employs the computer-aided simulation and experimental approach to investigate the machinability of Al 6065 T6 using response surface methodology (RSM) during milling operation. The RSM was implemented in the Design Expert 2022 environment and the designed experiment produced 20 experimental trials whose responses specifically, maximum contact stress, reaction force, and surface roughness determined via modelling and simulation in the Complete Abaqus Environment (CAE). The validation of the numerical analysis was done by conducting physical experimentations. This established the feasible range of process parameters that can ensure effective machinability of Al 6065 T6 during milling operation. The values of the process parameters that produced the least surface roughness for both the computer-aided simulation and experimental approaches are feed rate (0.07 mm/rev), cutting speed (15 m/min), and tool slip factor (25%). Furthermore, predictive models were developed for estimating the magnitude of maximum contact stress, reaction force, and surface roughness. The statistical analysis of the predictive models indicates that they are suitable for predictive purposes. The outcome of this study adds to the understanding of the machinability of Al 6065 T6. The empirical results can assist machinists to develop products from Al 6065 T6 that will meet the required service requirements.